2018
DOI: 10.1103/physrevb.97.155436
|View full text |Cite
|
Sign up to set email alerts
|

Work function and quantum efficiency study of metal oxide thin films on Ag(100)

Abstract: Increasing the quantum efficiency (QE) of metal photocathodes is in the design and development of photocathodes for free-electron laser applications. The growth of metal oxide thin films on certain metal surfaces has previously been shown to reduce the work function (WF). Using a photoemission model B. Camino et al. [Comput. Mater. Sci. 122, 331 (2016)] based on the three-step model combined with density functional theory calculations we predict that the growth of a finite number of MgO(100) or BaO(100) layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 35 publications
2
10
0
Order By: Relevance
“…In this paper we show the potential, predicted by Chang [4], of ultra-thin MgO film metal photocathodes. The photocathodes presented exhibit a WF reduction of more than 1 eV relative to the substrate and an increase in QE of more than an order of magnitude.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…In this paper we show the potential, predicted by Chang [4], of ultra-thin MgO film metal photocathodes. The photocathodes presented exhibit a WF reduction of more than 1 eV relative to the substrate and an increase in QE of more than an order of magnitude.…”
Section: Discussionmentioning
confidence: 80%
“…One possible method of improving the performance of photocathodes is by the use of surface preparation or treatment, lowering the surface WF and increasing the QE. Surface dielectric films on metals have been shown to produce a surface with a lower WF [3] and previous works [4,5] on MgO thin films on Ag(100) have demonstrated this reduction in WF and the potential for QE enhancement. Therefore, MgO films have the potential to improve the QE, while simultaneously increasing the robustness of the sample due to the chemical stability of MgO forming an overlayer to protect from residual gases in the system.…”
Section: Introductionmentioning
confidence: 87%
“…The lower WF for a 1-ML covering is due to the formation of a nonpolar BaO monolayer. Experimental and theoretical studies of metal oxide thin films on metal surfaces has shown that the metal oxide thin film tends to reduce the WF of the metal substrate [5,46,47]. This effect The adsorption of oxygen on the hollow sites of the lowest formation-energy surface of both alloys is energetically favorable.…”
Section: E Oxygen Adsorptionmentioning
confidence: 99%
“…Numerous techniques have been trialed to reduce the WF and increase the QE of metal photocathodes. Recent examples include coating them with atomically thin twodimensional (2D) nanomaterials [4], and using computational design to simulate oxide thin films such as MgO and BaO on Ag(100) [5].…”
Section: Introductionmentioning
confidence: 99%
“…For the current case of Au–Ag, MgO can serve as one of the excellent buffer materials because it has very good lattice matching with the metals (the cubic structure with the lattice constant ∼4.21 Å) and is highly insulating with a high band gap ∼8 eV . In the literature, it has also been shown that when ultrathin MgO is introduced on the metal thin films, the work function of metal films can be tuned, which affects the quantum efficiency and hence the optoelectronic properties. Moreover, in thin film growth, an ultrathin MgO layer can also facilitate the initial nucleation and promotes lateral growth that results in the smooth surface morphology and layer-by-layer growth. , Recently, it has also been shown that the MgO passivation film acts as a protective layer for enhanced photoelectric performances, indicating the importance of insulating buffer layers for high-performance photovoltaic devices. , All these studies suggest that understanding and control of the interfacial charge-transfer process of halide perovskite integrated with the bimetallic plasmonic Au–Ag nanostructure and an insulating layer in-between are extremely important for future high-performance optoelectronic devices, for example, halide perovskite-based solar cells and light-emitting diodes.…”
Section: Introductionmentioning
confidence: 99%